In vitro and in vivo antimicrobial activity of the fungal metabolite toluquinol against phytopathogenic bacteria - Chung, Dawoon; Nguyen, Hoa Thi; Yu, Nan Hee; Yu, Woon-Jong; Kwon, Yong Min; Bae, Seung Seob; Choi, Grace; Kim, Jin-Cheol (Frontiers in Microbiology, 2023)
Introduction: Bacterial plant diseases cause tremendous economic losses worldwide. However, a few effective and sustainable control methods are currently available. To discover novel and effective management approaches, we screened marine fungi for their antibacterial activity against phytopathogenic bacteria in vitro and in vivo. Methods: We screened culture broth of 55 fungal strains isolated from various marine sources (seawater, algae, sediment, etc.) for the in vitro antibacterial activity by the broth microdilution method. Then, only the fungal strain (designated UL-Ce9) with higher antibacterial activity in vitro was tested in an in vivo experiment against tomato bacterial wilt. The active compounds of UL-Ce9 were extracted using ethyl acetate, purified by a series of chromatography, and the structure was elucidated by nuclear magnetic resonance spectroscopy. Pesticide formulations of toluquinol were prepared as soluble concentrates and wettable powder. The disease control efficacy of toluquinol formulations was evaluated against leaf blight of rice and bacterial wilt of tomato. Results and Discussion: The culture broth of UL-Ce9 showed high antibacterial activity against Agrobacterium tumefaciens, Ralstonia solanacearum, and Xanthomonas arboricola pv. pruni in vitro, and we selected UL-Ce9 for the in vivo test. The UL-Ce9 culture broth completely suppressed bacterial wilt of tomato at a dilution of 1:5. The phylogenetic analysis identified UL-Ce9 as Penicillium griseofulvum, and the antibacterial metabolites were revealed as patulin, gentisyl alcohol, and toluquinol, all of which were associated with the biosynthetic pathway of the mycotoxin patulin. Patulin exhibited the highest antibacterial activity against 16 phytopathogenic bacteria in vitro, followed by toluquinol and gentisyl alcohol. As patulin is toxic, we selected toluquinol to investigate its potential use as a pesticide against bacterial plant diseases. Compared with the chemicals currently being applied in agriculture (streptomycin and oxytetracycline), toluquinol formulations exhibited similar and higher control efficacies against bacterial leaf blight of rice and bacterial wilt of tomato, respectively. To the best of our knowledge, this is the first report of the antibacterial activity of toluquinol against phytopathogenic bacteria. Our results suggest that toluquinol is a potential candidate for the development of novel and effective pesticides for the management of bacterial plant diseases.